Organizational Citizenship Behavior Among Iranian Nurses - H Dargahi; S Alirezaie; G Shaham (Tehran University of Medical Sciences, 2012)
Background: Organizational Citizenship Behavior (OCB) is defined as "individual behavior that is discretionary, not directly or explicitly recognized by the formal reward system, and that in the aggregate, promotes the effective functioning of organization". OCB, enhance job satisfaction among nursing employees. According to several findings, nurses' OCB have a positive and significant influence on job satisfaction. This research is aimed to study OCB among Iranian nurses. Methods: A cross-sectional, descriptive and analytical study was conducted among 510 nurses working in 15 teaching hospitals in Tehran, Iran to be selected by stratified random sampling. The respondents were asked to complete Netemeyer's organizational citizenship behavior questionnaire that encompassed four dimensions of OCB including Sportsmanship, Civil Virtue, Conscientiousness, Altruism and selected each item of OCB dimensions and identified their attitudes about OCB items were observed in hospitals of Tehran. The data was analyzed by T-test, ANOVA and Pearson statistical methods. Results: The results of this research showed that most of the nurses who studied in this study, had OCB behaviors. Also, we found that there was significant correlation between Iranian nurses' marriage status, qualifications and gender with sportsmanship, altruism and civic virtue. Conclusion: This research demonstrates the existence of OCB among Iranian nurses that are essential in developing patient - oriented behavior. The results can be used to develop further nursing management strategies for enhancement of OCB. Finally, the present study indicates new possibilities for future researches such as analysis and comparison of OCB between different hospitals and how nursing policy-makers can enhance these behaviors in Iranian hospitals.